INTERNET AND EXTRANET (INTERNATIONAL CONFERENCE OF NATURAL AND SOCIAL-HUMANITARIAN SCIENCES, 2025)
Internet and Extranet are the two very important elements of modern communication and sharing of information. The Internet is a universal network uniting millions of devices across the world whereas the Extranet is a limited expansion of the internal network of the organization which allows secure cooperation with external partners. This paper explains the design, usage, and uses of the two systems with a keen focus on their use in the global connectivity, business activities, and protection of information.